Viability of Hemoglobin Concentration, Red Blood Cells, White Blood Cells and Platelets Counts in Blood Specimens Stored Overnight at Room Temperature - Masud, Kamran; Kamran, Harris; Kamran, Maryam; Akhtar, Samar; Ahmad, Hamaad; Gul, Rabia (International Journal of Pathology, 2018)
Introduction: Delayed analysis in pathology laboratories is a common problem because of large number of samples to be tested every day. But this delay causes sample aging and affects directly diagnostic test results. Complete blood picture is most widely done test in laboratory analysis provides basic information regarding diagnosis as well as monitoring of patient’s health. So, accuracy of such diagnostic test is very important to assure correct diagnosis that leads to right therapy.Objective: The aim of current research work is to evaluate the viability of blood specimen for complete blood count at different time intervals at room temperature.Patients and Methods: For this purpose, 128 samples were collected during routine laboratory work at the different time of the year. Collected samples were analyzed at the time of collection and after 24 hours. Parameters studied includes hemoglobin concentration, RBC counts, WBC counts and Platelets counts. Results were analyzed by using student T-test.Results: Parameters Hemoglobin concentration, RBC, and WBC remain stable over 24 hours at room temperature as there was no statistically significant difference between fresh and delayed sample. However, Platelets values differed significantly (p<0.05) and indicate that this parameter needs special storage in case of delayed analysis.Conclusion: Thus, it is concluded that forPlatelet counts sample requires special storage conditions to assure reliable results. While only hemoglobin concentration, RBC and WBC counts can be accurately measured even after 24 hours at room temperature.